Characterization of PLA nanofiber structures containing herbal extracts - Eroglu, Nilsen Sunter; Canoglu, Suat (European Journal of Chemistry, 2022)
The use of renewable, sustainable, and biocompatible products without chemical side effects is increasing day by day in antibacterial applications instead of materials that harm nature and humans. In biomedicine, antibacterial nanofiber composite surfaces with generally produced from materials with antibacterial properties such as chitosan, hyaluronic acid, collagen, and silver nanoparticles. In this study, olive leaf, terebinth, and fumitory plants and biocompatible, biodegradable, and environmentally friendly polylactic acid (PLA) polymer were used to obtain nanofiber structures with 100% plant extracts. Viscosity and conductivity of solutions prepared with optimum properties were analysed, the nanofiber material was produced in solution with electrospinning method, and the morphological evaluation and mechanical measurement of the nanofiber material were performed. Finally, bacterial exchange analyses were performed before and after incubation in the UV-VIS spectrophotometer. As a result of the study, the thinnest and the most uniform fiber materials were found in CFO (consist of PLA (C1) and fumitory (FO)) coded nanofiber material, the best strength values were found in COE (consist of PLA (C1) and olive leaf (OE)) coded nanofiber structure, and the highest bacterial exchange was observed in CFO coded nanofiber material. Based on these results, it has been suggested that the CFO coded nanofiber structure can be used in biomedicine. It has been observed that olive leaf, terebinth, and fumitory plant extracts, which can be grown easily in every region in Turkey, have a significant level of bacterial resistance. In conclusion, fumitory and terebinth plants can be used in antibacterial agent applications since they allow obtaining smooth and uniform nanofiber structures, and thanks to their high bacteria nullification properties.